Security in Peaceful Coexistence in Faith | الأمن في التعايش السلمي في العقيدة - Ahmaddin Ahmad Tohar (Al-Zahra : Journal for Islamic and Arabic Studies, 2017)
Having religion is both fitrah and human rights at the same time. Although Islam has taught people about the right and wrong religion, people are given the freedom to choose a religion, no one can force others to embrace a particular religion. Islam promotes peace and coexistence with different religions. Attacks on other religions are a sign that the religion’s position is being pushed in society.